2016
DOI: 10.1017/cnj.2016.27
|View full text |Cite
|
Sign up to set email alerts
|

Variable future-time reference in French: A comparison of learners in a study-abroad and a foreign-language context

Abstract: This study seeks to advance understanding of second-language (L2) acquisition of future-time reference in French, by comparing the developmental trajectories of learners living in and away from the target-language setting. Study-abroad learners in France (n= 45), foreign-language learners living in the US (n= 37), and native speakers of Hexagonal French (n= 30) participated in this study. They completed a written-contextualized task, a language-proficiency test and a background questionnaire. For each written-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…To our knowledge, the current study is the first to include three separate forms in a single statistical model of variable future-time reference in French oral production (see Edmonds and Gudmestad (2015) and Gudmestad and Edmonds (2016) for written data). We argue that unless the futurate present occurs marginally in a given dataset, an analysis that includes just two of these forms results in an incomplete understanding of variable FTR.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, the current study is the first to include three separate forms in a single statistical model of variable future-time reference in French oral production (see Edmonds and Gudmestad (2015) and Gudmestad and Edmonds (2016) for written data). We argue that unless the futurate present occurs marginally in a given dataset, an analysis that includes just two of these forms results in an incomplete understanding of variable FTR.…”
Section: Methodsmentioning
confidence: 99%
“…Namely, this body of work has shown similarities to NS research in that clause type, temporal distance, and temporal adverbials have significantly predicted learner future‐time expression (Gudmestad & Geeslin, , ; Kanwit, ; Kanwit & Solon, ; Solon & Kanwit, ). Similarly, research on L2 French variation has demonstrated that learners begin with high rates of the PI before shifting to the use of additional forms, such as the PF and MF, and that learner use of temporal adverbials is differentially distributed across future‐time forms (Gudmestad & Edmonds, ; Moses, ; Schlyter, ). Additional insights on the L2 acquisition of futurity will be considered in light of lexical futures in the following section.…”
Section: Variationist Studies Of L1 and L2 Romance Futuritymentioning
confidence: 99%